Pauline challenge to African masculinities : reading Pauline texts in the context of HIV/AIDS : hope for HIV/Aids patients - Togarasei, Lovemore (Acta Theologica, 2012)
This article discusses Pauline masculinity in the context of HIV/AIDS. If any success against HIV/AIDS is to be achieved, men need to be constructively involved in this struggle rather than merely being vilified. It is directed towards those who want to live by the ideals set by Paul. The article argues that in many ways Paul challenges dangerous masculinities and that, if his challenge is taken seriously, Christian communities may witness a decline in HIV prevalence. The article focuses specifically on Paul's teaching on marriage and sex.
Free